Assessing foundation students’ acceptance in using video conferencing technologies (VCTs) as online learning platforms during the pandemic / Mohd Hafizul Ismail, Sallaudin Hassan and Siti Nur Dina Mohd Ali - Ismail, Mohd Hafizul; Hassan, Sallaudin; Mohd Ali, Siti Nur Dina (Universiti Teknologi MARA, 2023)
The COVID-19 pandemic has significantly affected Higher Education Institutions (HEIs) in Malaysian education system. Due to this, the HEIs have implemented online learning to be replaced with physical classrooms to ensure that all students able to reach their learning potentials. As such, video conferencing technologies (VCTs) have been employed nationwide for effective learning activities. Previous research have shown that teaching and learning using VCTs are beneficial for online learning, however, not many studies focused on the student’s acceptance of VCTs during unforeseen situations. This study intends to overcome this research gap by investigating the factors influencing the foundation students’ acceptance of VCTs during the outbreak. Therefore, the facilitating conditions and computer self-efficacy factors are integrated into the Technology Acceptance Model (TAM) for analysis. For this purpose, the PLS-SEM was used to analyze the data collected from 231 participants of selected higher education institutions in Malaysia. The finding revealed that ‘attitude towards use’ and ‘intention to use’ VCTS have a positive relationship with the actual use of VCTs. Furthermore, the result indicated that facilitating condition has significantly impacted the ‘perceived ease of use’ of the VCTs. However, ‘computer self-efficacy’ has no significant impact on the ‘perceived usefulness’ of the VCTs. It is also learned that using VCTs is acceptable for remote and online learning mode, particularly amid the current COVID-19 pandemic. The outcomes of this study are able to improve the existing knowledge on the student’s acceptance of VCTs and provide useful insights into the curriculum designated for the HEIs. Hence, it can be concluded that our findings validated the model used in this study and offered valuable guidelines in developing online learning approaches that promote learning through varied platforms.